Students' Attitude Towards Translanguaging Practice in Indonesian EFL Classes - Fransiskus Dinang Raja; Suparno Suparno; Ngadiso Ngadiso (AL-ISHLAH: Jurnal Pendidikan, 2022)
The multilingual world demands educational stakeholders to adjust by embracing multilingual pedagogies. Translanguaging is deemed a prominent language practice to be implemented in educational settings, especially in the EFL class. However, the practice still obtains criticisms. Many scholars point out challenges in implementing classroom translanguaging. Therefore, studying attitudes, specifically students' attitudes, becomes significant at this point because it helps to reveal how students' feelings and thoughts of translanguaging practice are based on their learning experience. Further, their attitudes can be considered in the classroom decision making whether to translanguage or not to translanguage. The present study will generally continue what previous scholars have done but in a new context and methodology. This study investigated students' attitudes towards student- and teacher-directed translanguaging in Indonesian EFL classrooms. The participants were 40 grade VIII students from two EFL classes of a private boarding school located in East Nusa Tenggara, Indonesia. The data was collected using online questionnaires consisting of close-ended and mainly open-ended questions. The result showed that most students expressed negative feelings toward students-directed translanguaging. Meanwhile, teacher-directed translanguaging was more acceptable indicated by most students who had positive feelings towards their teachers' translanguaging. Students' arguments and comments were also interesting to be noticed. These findings shed light on a multilingual pedagogical practice and further research, which we would like to discuss further within this article.